Platform Partnership Programs and Content Supply: Evidence from the YouTube "Adpocalypse" - Lena Abou El-Komboz; Anna Kerkhof; Johannes Loh (Center for Economic Studies and ifo Institute (CESifo), 2023)
Many digital platform host content produced by independent creators and rely on advertising as their primary source of revenues. They commonly use partnership programs to put into place incentives for creators to produce high-quality content by sharing part of the advertising revenue with them. In addition, these programs let them exercise control over their participation to prevent the presence of "bad-faith" actors who can otherwise harm the integrity of the platform. However, the rules governing access to such programs may have to be adjusted over time, which in turn may disrupt creators' motivation to produce content. This paper studies a rule change on YouTube that made access to its partner program more restrictive. This also removed all former participants who did not meet the new requirements and made it impossible for them to continue commercializing their content on the platform. Using a regression discontinuity design, we provide causal evidence that affected creators subsequently reduced the frequency of their uploads and provided content of lower quality and diversity. We also investigate and discuss effect heterogeneity between mainstream and niche as well as more and less experienced creators to learn about the underlying financial and non-pecuniary motivations. Our findings provide novel insights about the effective governance of ad-based platforms using partnership programs.
Keywords: 330; platform governance; partnership programs; content supply; ad-based business models; access restrictions